Local Food Tuna into Shredded in Nusa Lembongan-Bali (Processing, Hedonic Test, and Nutrition) - Ni Putu Eka Trisdayanti; I Made Purwa Dana Atmaja; Made Hendrayana (Universitas Pendidikan Indonesia, 2023)
There is no further processing of tuna in Nusa Lembongan, so if it is not sold out, tuna will rot and be thrown away, even though the protein content is high, the price is affordable. To overcome this, it is necessary to process tuna, so that later it can have a long shelf life, high economic value. Based on these problems, a research was conducted on the processing of local tuna tuna in Nusa Lembongan into shredded, then measuring the level of consumer preference and testing the nutrition. This research method is experiment, hedonic test with 50 panelists, and nutrition test at Udayana University Analytical Laboratory. The data analysis technique of this research is descriptive qualitative. The results of the research on the ingredients for making tuna shredded are clean tuna, thick coconut milk, liquid coconut milk, shallots, garlic, red chilies, galangal, ginger, turmeric, coriander, sugar, salt, pepper, lime leaves, and coriander leaves. regards. The results of the hedonic test of shredded tuna from 50 panelists in Nusa Lembongan showed that most answered LIKE shredded tuna in terms of taste, aroma, texture, and color. The results of the nutritional test for shredded tuna showed that 100 grams of shredded tuna contained 30.33 grams of carbohydrates, 37.44 grams of protein, 30.36 grams of fat and 503.327 kcal.Keywords: shredded, tuna, processing, hedonic, nutrition